ANALISIS PENGARUH KURS, PEMBIAYAAN, CURRENT RATIO DAN BEBAN OPERASIONAL PENDAPATAN OPERASIONAL (BOPO) TERHADAP NON PERFORMING FINANCING ( NPF ) - Wahyuni, Ayu Dwi; Ciptaningsih, Rokhmah Agus (JURNAL EKONOMI, 2021)
This study aims to analyze the Exchange Rate, Financing, Current Ratio and Operating Income Operating Expenses (BOPO) to Non Performing Financing (NPF) listed on the Indonesia Stock Exchange for 6 years from 2014-2019. The population of this research is Bank Syariah Mandiri which is listed on the Indonesia Stock Exchange for the period 2014-2019. The sampling technique used the purposive sampling method at Bank Syariah Mandiri for the period 2014-2019 quarterly I-IV financial statements that were used as samples. Statistical analysis in this study uses quantitative data and is processed by multiple regression analysis. The results of this study indicate that: Exchange rate has no effect on NPF, Financing has no effect on NPF, Current Ratio has no effect on NPF, Operating expenses for operating income (BOPO) has an effect on NPF. Simultaneously Exchange Rate, Financing, Current Ratio, Operating Income Operating Expenses (BOPO) together affect the NPF. Suggestions that can be given are as follows: 1. This research is expected to provide useful information for customers. 2. For further researchers to have more variables so that they can provide more accurate research results. Keywords : Exchange Rate, Financing, Current Ratio, Operating Expenses to Operating Income (BOPO) and Non Performing Financing (NPF).